Strategic urban and regional planning - Kühn, Manfred (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The term „strategic planning” is increasingly used in German planning theory but in a very ambiguous way. For ones, the revival of strategic planning offers hopes for a third way between comprehensive and incremental planning. For others strategic planning is actually a fuzzy concept and rather “old wine in new bottles”. The main aim of the paper is to construct a new model of strategic urban and regional planning and to prove this by empirical analysis of approaches and problems in application. Therefore the first part of the paper tries a positioning of strategic planning within theoretical discourses: some definitions from international planning theories are presented, and differences between incremental and comprehensive planning models are pointed out. Part 2 provides a normative model of strategic planning with main elements: how should strategic planning be to fulfil different demands? Part 3 describes contexts, approaches and some experiences of the application of strategic visions and projects in the management of spatial changes of cities and regions in decline. Finally in part 4, the model of strategic urban and regional planning will be reflected in a critical way.
Keywords: City and regional planning; Strategie visions; Strategie projects; Planning models; Planning theory